Novel self-adhesive catalyst coating and application of novel self-adhesive catalyst coating in metal-based monolithic catalyst
By adopting a new self-adhesive catalyst coating on the metal-based integral catalyst, the hydrophobicity of silicone rubber and the effect of tackifier are used to solve the problem of poor performance of the catalyst under water vapor conditions, and efficient toluene decomposition and good bonding effects are achieved.
Patent Information
- Application Number
- CN202411841885.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-03-14
AI Technical Summary
In practical applications, metal-based monolithic catalysts have problems such as low coating firmness and poor water resistance, which leads to poor catalytic performance under water vapor conditions.
Using a new self-adhesive catalyst coating, by introducing silicone rubber as a mobile phase into the coating precursor and adding components such as tackifiers to enhance the binding force between the catalyst and the metal matrix, and reducing the competitive adsorption between water molecules and toluene molecules through the hydrophobicity of the silicone rubber.
The toluene decomposition rate of the catalyst under water vapor conditions is significantly improved, and the adhesion effect and water resistance of the catalyst are improved. The weight loss rate is 0.22% to 0.81%, and the toluene purification efficiency is more than 90%.
Smart Images

Figure CN119608246A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of volatile organic pollutant catalysis, and in particular to a novel self-adhesive catalyst coating and application thereof in a metal-based integral catalyst. Background Art
[0002] Volatile organic compounds (VOCs), such as toluene and formaldehyde, are harmful to human health, irritate the skin, eyes and respiratory tract, cause headaches, pneumonia and even have the risk of cancer. At the same time, they damage the ecological environment and are one of the important precursors of ozone and secondary organic aerosol pollution. Therefore, there is an urgent need to develop effective methods to eliminate indoor ozone to protect human health from the increasing exposure to VOCs in the environment. Among the many technologies for controlling VOCs pollution, catalytic oxidation has been widely used due to its mild use conditions, high purification efficiency and low cost. Precious metal catalysts such as Pt (Xiao, Chen et al. 2022) and Pd (Jinglei, Cui et al. 2024) have excellent catalytic degradation ability for VOCs. However, in practical applications, these powder catalysts usually need to be further made into particles or coated on porous carriers, making the preparation steps of monolithic catalysts cumbersome. Metal-based monolithic catalysts have more advantages in application than powder catalysts and particle catalysts due to their small size, low pressure drop and high mass and heat transfer efficiency. However, due to the smooth surface and small specific surface area of the metal substrate, and the mismatch in thermal expansion coefficients between the catalyst ceramic coating and the substrate, there are problems such as the coating's low firmness on the metal substrate and poor water resistance in practical applications.
[0003] For example, CN112999987B discloses an electrically heated monolithic metal-based catalytic reactor and a preparation method thereof, which has complicated loading process steps. First, a layer of Al2O3 whiskers is oxidized on the FeCrAl metal substrate by air oxidation treatment, and then a layer of Al2O3 carrier coating is applied on the oxidized substrate by a widely used suspension deposition method, and finally the required active components are loaded on the metal substrate with the carrier coating, and the monolithic catalyst is prepared by drying. Summary of the invention
[0004] In order to overcome the shortcomings and deficiencies of the above-mentioned technology, one of the purposes of the present invention is to provide a new self-adhesive catalyst coating and its application in metal-based integral catalysts. Through the catalyst obtained by the present invention, the coating precursor uses silicone rubber as the mobile phase, and more viscosity enhancers can be introduced to enhance the bonding strength between the catalytic coating and the metal substrate. At the same time, silicone rubber is hydrophobic, which weakens the competitive adsorption of water molecules and toluene molecules, thereby improving the toluene decomposition rate of the catalyst under water vapor conditions.
[0005] To achieve this object, the present invention adopts the following technical solutions: In a first aspect, the present invention provides a novel self-adhesive catalyst coating, wherein the coating comprises the following components by mass fraction: 30-80% by mass of vinyl silicone oil, 15-60% by mass of carrier filler, 1-10% by mass of coupling agent, 1-10% by mass of tackifier, 1-10% by mass of cross-linking agent, 0.01-0.5% by mass of cross-linking inhibitor, and 0.1-5% by mass of cross-linking catalyst.
[0006] As a preferred technical solution of the present invention, the vinyl silicone oil is α, ω-divinyl polydimethylsiloxane; the viscosity of the α, ω-divinyl polydimethylsiloxane at 25° C. is 50 mPa.s to 100000 mPa.s.
[0007] As a preferred technical solution of the present invention, the carrier filler is a mixture of one or more of fumed silica, precipitated silica, alumina, calcium carbonate, and short fibers; the specific surface area of the carrier filler is 100-400 g / cm 3 .
[0008] As a preferred technical solution of the present invention, the coupling agent is one or a mixture of two or more of hexamethyldisilazane, hexamethyldisiloxane, KH550 and hydroxy silicone oil.
[0009] As a preferred technical solution of the present invention, the tackifier is one or a mixture of two or more of ethylene-vinyl acetate copolymer, 1,3,5,7-tetramethylcyclotetrasiloxane and polyvinyl alcohol copolymer.
[0010] As a preferred technical solution of the present invention, the cross-linking agent is hydrogen-containing silicone oil; the hydrogen content of the hydrogen-containing silicone oil is 0.10%-1.55%.
[0011] As a preferred technical solution of the present invention, the cross-linking inhibitor is one or a mixture of two or more of 3-methyl-1-butyn-3-ol, 1-ethynylcyclohexanol, and tetramethyltetravinylcyclotetrasiloxane.
[0012] In a second aspect, the present invention provides a method for preparing a novel self-adhesive metal-based monolithic catalyst, the preparation method comprising the following steps: (A1) Weigh appropriate amounts of resin, carrier filler and tackifier according to the ratio of raw materials; (B1) mixing the resin and the carrier filler in a power mixer, and grinding until the carrier filler is evenly dispersed; (C1) evacuating the mixture in step B in a power mixer and stirring evenly, cooling to room temperature, adding a tackifier and a coupling agent and mixing evenly, adding a catalyst and an inhibitor, stirring evenly, and obtaining a self-adhesive catalyst coating precursor; (D1) spraying the mixture of step C on the treated substrate surface using a spray gun, and then drying at 80 to 120° C. for 5 to 180 min to obtain a metal honeycomb substrate-coating structure on the metal honeycomb substrate; (E1) The metal honeycomb substrate-coating structure is immersed in an excess active component salt solution for 0.5 to 10 hours, and dried in an oven at 50 to 150° C. for 2 to 15 hours to obtain a self-adhesive metal-based monolithic catalyst with catalytic activity.
[0013] The preparation method may also include the following steps: (A2) Resin, carrier filler and tackifier weighed according to the ratio of raw materials; (B2) Immersing the carrier filler in an excess amount of active component salt solution for 0.5 to 10 hours, and drying in an oven at 50 to 150° C. for 2 to 15 hours to obtain a carrier filler having catalytic activity. (C2) mixing the resin and the carrier filler having catalytic activity in a power mixer, and grinding until the carrier filler is evenly dispersed; (D2) evacuating the mixture in step C in a power mixer and stirring evenly, cooling to room temperature, adding a tackifier and a coupling agent and mixing evenly, adding a catalyst and an inhibitor, and stirring evenly to obtain a self-adhesive catalyst coating precursor; (E2) Spraying the mixture of step D on the surface of a metal substrate using a spray gun, followed by drying at 80 to 120° C. for 5 to 180 min to obtain a self-adhesive metal-based monolithic catalyst having catalytic activity.
[0014] As a preferred technical solution of the present invention, the catalyst can be composed of three parts: a matrix, a carrier and an active component, wherein the carrier is loaded on a metal matrix, the active component is loaded on the carrier, and is prepared into a self-bonding metal-based catalyst; or the three parts can be non-integrally integrated together, such as the carrier and the active component are prepared as a whole, and the matrix independently plays a heat transfer role.
[0015] The active component precursor can be a nitrate of platinum, palladium, silver, manganese, nickel or other chemical elements, or a sulfate or chlorate, or a mixture of two or more, or a catalyst active component with equivalent functions.
[0016] The loading methods of the active components include impregnation, slurry, spraying and integrated molding. The solvent used to prepare the active component precursor solution is deionized water, ethanol or other organic solvents.
[0017] As a preferred technical solution of the present invention, the weight loss rate of the metal-based integral catalyst is 0.22% to 0.81%, and the purification efficiency of toluene under water vapor conditions is above 90%. The beneficial effects of the present invention are: 1. In the obtained self-bonding metal-based integral catalyst, the coating precursor uses silicone rubber as the mobile phase, introduces more viscosity enhancers, and solidifies at high temperature to form a coating, thereby enhancing the bonding effect between the catalyst coating and the metal; after the coating is solidified, a layer of silicone rubber is formed in the carrier filler, and the silicone rubber is hydrophobic, which increases the adsorption energy of water on the catalyst surface, while being beneficial to the adsorption of toluene molecules, thereby weakening the competitive adsorption between water molecules and toluene molecules on the active sites, and improving the catalyst's ability to decompose toluene under water vapor.
[0018] 2. The weight loss rate of the obtained metal-based monolithic self-adhesive catalyst is 0.22% to 0.81%, and the purification efficiency of toluene under water vapor conditions is more than 90%. BRIEF DESCRIPTION OF THE DRAWINGS Figure 1 : Comparison chart of the water vapor resistance of the self-adhesive metal-based monolithic catalyst prepared by the present invention. DETAILED DESCRIPTION
[0019] The following will be combined with the specific embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. The embodiments described are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work belong to the protection scope of the present invention.
[0020] Weight loss rate test: The catalyst precursor is applied to the metal honeycomb sample, and then cured at high temperature to obtain a coating. First, the adhesion of the coating is tested using ultrasound. The metal sample coated with the catalyst coating is placed in a sampling tube filled with petroleum ether, and then treated in a 40Hz / 800W ultrasonic water bath for 30 minutes. Weigh the weight after drying. After ultrasonic treatment, use thermal shock to test the adhesion of the coating. The ultrasonically treated metal sample is placed in a muffle furnace at 500°C for 90 minutes, and then directly taken out and exposed to the air. Weigh the weight after cooling. The weight loss rate of the catalyst coating is expressed as a percentage of the weight difference before and after the sample weight loss test to the original weight.
[0021] Toluene purification efficiency test under water vapor conditions: The active components are loaded onto the metal honeycomb sample of the bonding coating, and then dried to obtain a self-adhesive metal-based monolithic catalyst. First, the catalyst is placed in a glass tube of a heating furnace to form a reactor. Then, 1000ppm toluene standard gas is passed into a water vapor generator and a 150°C reactor in sequence. The catalyst catalytically decomposes toluene in a reactor at 150°C and high humidity (90% relative humidity). Subsequently, the tail gas after the reaction is passed into a gas chromatograph to detect the concentration of the remaining toluene, and the toluene decomposition efficiency of the catalyst under water vapor is expressed as a percentage of the ratio of the toluene concentration difference to the original toluene concentration. Under other identical conditions, the performance of the catalyst is tested in a reactor with low humidity (30% relative humidity).
[0022] A novel self-adhesive catalyst coating comprises the following components in mass fractions: 30-65% vinyl silicone oil, 15-60% carrier filler, 1-10% coupling agent, 1-10% tackifier, 1-10% crosslinking agent, 0.01-0.5% crosslinking inhibitor, 0.1-5% crosslinking catalyst; The vinyl silicone oil is α, ω-divinyl polydimethylsiloxane; the viscosity of the α, ω-divinyl polydimethylsiloxane at 25° C. is 50 mPa.s to 100000 mPa.s; The carrier filler is a mixture of one or more of fumed silica, precipitated silica, alumina, calcium carbonate, and short fibers; the specific surface area of the carrier filler is 100-400 g / cm 3 ; The coupling agent is one or a mixture of two or more of hexamethyldisilazane, hexamethyldisiloxane, KH550 and hydroxy silicone oil; The tackifier is one or a mixture of two or more of ethylene-vinyl acetate copolymer, 1,3,5,7-tetramethylcyclotetrasiloxane and polyvinyl alcohol copolymer; The cross-linking agent is hydrogen-containing silicone oil; the hydrogen content of the hydrogen-containing silicone oil is 0.10%-1.55%; The cross-linking inhibitor is one or a mixture of two or more of 3-methyl-1-butyn-3-ol, 1-ethynylcyclohexanol, and tetramethyltetravinylcyclotetrasiloxane; The cross-linking catalyst is a platinum catalyst; the platinum content of the platinum catalyst is 2500ppm to 6000ppm.
[0023] The method for preparing a self-bonding metal-based monolithic catalyst comprises the following steps: (A) Weigh appropriate amounts of resin, carrier filler and tackifier according to the ratio of raw materials; (B) mixing the resin and the carrier filler in a power mixer, and grinding them using a three-roll mill until the carrier filler is evenly dispersed; (C) evacuating the mixture in step B in a power mixer and stirring evenly, cooling to room temperature, adding a tackifier and a coupling agent and mixing evenly, adding a catalyst and an inhibitor, stirring evenly, and obtaining a self-adhesive catalyst coating precursor; (D) spraying the mixture of step C on the treated substrate surface using a spray gun, followed by drying at 80 to 120° C. for 5 to 180 min to obtain a catalyst coating on the metal honeycomb substrate; (E) The self-adhesive catalyst coating is immersed in an excess active component salt solution for 0.5 to 10 hours, and dried in an oven at 50 to 150° C. for 2 to 15 hours to obtain a self-adhesive metal-based monolithic catalyst with catalytic activity.
[0024] The catalyst may comprise a matrix, a carrier and an active component, wherein the carrier is loaded on a metal matrix, the active component is loaded on the carrier, and the catalyst is prepared into a self-bonding metal-based catalyst; or the three parts may be non-integrally integrated together, such as the carrier and the active component are prepared as a whole, while the matrix independently plays a heat transfer role.
[0025] The active component precursor can be a nitrate of platinum, palladium, silver, manganese, nickel or other chemical elements, or a sulfate or chlorate, or a mixture of two or more, or a catalyst active component with equivalent functions.
[0026] The loading methods of the active components include impregnation, slurry, spraying and integrated molding. The solvent used to prepare the active component precursor solution is deionized water, ethanol or other organic solvents.
[0027] The weight loss rate of the metal-based integral catalyst is 0.22% to 0.81%, and the purification efficiency of toluene under water vapor conditions is above 90%.
[0028] Example 1 A novel self-adhesive catalyst coating comprises the following components in mass fractions: 45% vinyl silicone oil, 35% carrier filler, 5% coupling agent, 5% tackifier, 7% crosslinking agent, 0.3% crosslinking inhibitor, 2.7% crosslinking catalyst; The vinyl silicone oil is 10000mPa s α, ω-divinyl polydimethylsiloxane; The carrier filler is alumina; the specific surface area is 200 g / cm 3 ; The coupling agent is hexamethyldisilazane; The tackifier is polyvinyl alcohol poly-1000; The cross-linking agent is hydrogen-containing silicone oil; the hydrogen content of the hydrogen-containing silicone oil is 0.87%; The cross-linking inhibitor is 3-methyl-1-butyn-3-ol; The cross-linking catalyst is a platinum catalyst; the platinum content of the platinum catalyst is 3000 ppm.
[0029] The method for preparing a self-bonding metal-based monolithic catalyst comprises the following steps: (A) Weigh appropriate amounts of resin, carrier filler and tackifier according to the ratio of raw materials; (B) mixing the resin and the carrier filler in a power mixer, and grinding them using a three-roll mill until the carrier filler is evenly dispersed; (C) evacuating the mixture in step B in a power mixer and stirring evenly, cooling to room temperature, adding a tackifier and a coupling agent and mixing evenly, adding a catalyst and an inhibitor, stirring evenly, and obtaining a self-adhesive catalyst coating precursor; (D) spraying the mixture of step C on the treated substrate surface using a spray gun, followed by drying at 120° C. for 5 min to obtain a catalyst coating on the metal honeycomb substrate; (E) The self-adhesive catalyst coating is immersed in an excess active component salt solution for 5 hours and dried in an oven at 100° C. for 4 hours to obtain a self-adhesive metal-based monolithic catalyst with catalytic activity.
[0030] The metal matrix is a FeCrAl metal honeycomb.
[0031] The active component precursor is platinum. A self-bonded Pt / γ-Al2O3@FeCrAl metal honeycomb catalyst was obtained.
[0032] Example 2 A novel self-adhesive catalyst coating comprises the following components in mass fractions: 45% vinyl silicone oil, 35% carrier filler, 8% coupling agent, 4% tackifier, 5% crosslinking agent, 0.5% crosslinking inhibitor, 2.5% crosslinking catalyst; The vinyl silicone oil is α, ω-divinyl polydimethylsiloxane; the viscosity of the α, ω-divinyl polydimethylsiloxane at 25° C. is 70000 mPa.s; The carrier filler is precipitated white carbon black; the specific surface area of the carrier filler is 200 g / cm 3 ; The coupling agent is hexamethyldisilazane; The tackifier is 1,3,5,7-tetramethylcyclotetrasiloxane; The cross-linking agent is hydrogen-containing silicone oil; the hydrogen content of the hydrogen-containing silicone oil is 0.7%; The cross-linking inhibitor is 1-ethynyl cyclohexanol; The cross-linking catalyst is a platinum catalyst; the platinum content of the platinum catalyst is 5500 ppm.
[0033] The preparation method is the same as Example 1.
[0034] The metal matrix is a FeCrAl metal honeycomb; a self-adhesive Pd / Al2O3@FeCrAl metal honeycomb catalyst is obtained.
[0035] Example 3 A novel self-adhesive catalyst coating comprises the following components in mass fractions: 50% vinyl silicone oil, 40% carrier filler, 5% coupling agent, 4% tackifier, 3% crosslinking agent, 0.5% crosslinking inhibitor, 2.5% crosslinking catalyst; The vinyl silicone oil is α, ω-divinyl polydimethylsiloxane; the viscosity of the α, ω-divinyl polydimethylsiloxane at 25° C. is 1000 mPa.s; The carrier filler is a mixture of one or more of fumed silica, precipitated silica, alumina, calcium carbonate, and short fibers; the specific surface area of the carrier filler is 300 g / cm 3 ; The coupling agent is hexamethyldisiloxane; The tackifier is ethylene-vinyl acetate copolymer; The cross-linking agent is hydrogen-containing silicone oil; the hydrogen content of the hydrogen-containing silicone oil is 1.1%; The cross-linking inhibitor is tetramethyltetravinylcyclotetrasiloxane; The cross-linking catalyst is a platinum catalyst; the platinum content of the platinum catalyst is 4000 ppm.
[0036] The preparation method is the same as Example 1.
[0037] The metal matrix is a FeCrAl metal honeycomb; a self-adhesive Ag / SiO2(g)@FeCrAl metal honeycomb catalyst is obtained.
[0038] Comparative Example 1 The only difference from Example 1 is that no cross-linking agent is added, and the mass fraction of the cross-linking agent is partially filled by fillers. Others are the same as Example 1.
[0039] Comparative Example 2 The only difference from Example 1 is that no coupling agent is added, and the mass fraction of the coupling agent is partially filled by fillers. Others are the same as Example 1.
[0040] Comparative Example 3 The only difference from Example 1 is that no tackifier is added, and the mass fraction of the tackifier is partially filled by the filler. The rest is the same as Example 1.
[0041] Comparative Example 4 The only difference from Example 1 is that no crosslinking inhibitor is added, and the mass fraction of the crosslinking inhibitor is partially filled by fillers. Others are the same as Example 1.
[0042] Comparative Example 5 The only difference from Example 1 is that no vinyl silicone oil is added, and the mass fraction of the vinyl silicone oil is filled by pure water. Others are the same as Example 1.
[0043] The test data of each embodiment are shown in Table 1.
[0044] Table 1 Weight loss rate / % Decomposition rate of toluene at high humidity / % Decomposition rate of toluene at low humidity / % Difference in toluene decomposition rate between high and low humidity Example 1 0.5 94.2 96.2 2.0 Example 2 0.8 90.1 92.5 2.4 Example 3 0.2 93.1 98.2 5.1 Comparative Example 1 18.2 62.7 79.8 16.6 Comparative Example 2 0.9 80.5 82.5 2.0 Comparative Example 3 12.9 70.8 74.1 3.3 Comparative Example 4 1.2 85.1 86.2 1.1 Comparative Example 5 20.5 58.5 78.5 20.0 It can be seen from Example 1 and Comparative Examples 1 and 5 that the presence of a crosslinking agent and vinyl silicone oil significantly affects the weight loss rate of the catalyst; the crosslinking agent and vinyl silicone oil are cured to form a coating, the weight loss rate is low, and the catalytic efficiency is high. At the same time, compared with Comparative Examples 2, 3 and 4, Comparative Examples 1 and 5 are not cured to form a coating, and the difference in toluene decomposition rate under high humidity and low humidity is the largest. It can be seen from Example 1 and Comparative Example 2 that the use of a coupling agent will change the toluene decomposition rate of the catalyst under water vapor; the coupling agent can promote the dispersion of the carrier filler, thereby increasing the number of active sites of the catalyst and enhancing the catalytic activity. It can be seen from Example 1 and Comparative Example 3 that the tackifier can make the coating have a good bonding effect on the metal. It can be seen from Example 1 and Comparative Example 4 that the crosslinking inhibitor significantly affects the decomposition efficiency of toluene; the crosslinking inhibitor can extend the operating time of the coating precursor. The lack of a crosslinking inhibitor will cause the coating to cure prematurely, thereby causing the aggregation of the carrier filler, reducing the active sites, and reducing the catalytic efficiency.
[0045] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be thought of by a person skilled in the art within the technical scope disclosed by the present invention without creative work should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope defined in the claims.
Claims
1. A novel self-adhesive metal-based monolithic catalyst coating, characterized in that: The coating of the self-adhesive metal-based monolithic catalyst comprises the following components by mass fraction: 30-80% vinyl silicone oil, 15-60% carrier filler, 1-10% coupling agent, 1-10% tackifier, 1-10% cross-linking agent, 0.01-0.5% cross-linking inhibitor, 0.1-5% cross-linking catalyst.
2. The novel self-adhesive metal-based monolithic catalyst coating according to claim 1, characterized in that: The vinyl silicone oil is α, ω-divinyl polydimethylsiloxane; the viscosity of the α, ω-divinyl polydimethylsiloxane at 25° C. is 50 mPa.s to 100000 mPa.s.
3. The novel self-adhesive metal-based integral catalyst coating according to claim 1, characterized in that: The carrier filler is a mixture of one or more of fumed silica, precipitated silica, alumina, calcium carbonate, and short fibers; the specific surface area of the carrier filler is 100-400 g / cm 3 .
4. The novel self-adhesive metal-based integral catalyst coating according to claim 1, characterized in that: The coupling agent is hexamethyldisilazane, hexamethyldisiloxane, KH550 and hydroxy silicone oil, or a mixture of two or more thereof.
5. The novel self-adhesive metal-based integral catalyst coating according to claim 1, characterized in that: The tackifier is one or a mixture of two or more of ethylene-vinyl acetate copolymer, 1,3,5,7-tetramethylcyclotetrasiloxane and polyvinyl alcohol copolymer.
6. The novel self-adhesive metal-based integral catalyst coating according to claim 1, characterized in that: The cross-linking agent is hydrogen-containing silicone oil; the hydrogen content of the hydrogen-containing silicone oil is 0.10%-1.55%.
7. The novel self-adhesive metal-based integral catalyst coating according to claim 1, characterized in that: The cross-linking inhibitor is one or a mixture of two or more of 3-methyl-1-butyn-3-ol, 1-ethynylcyclohexanol, and tetramethyltetravinylcyclotetrasiloxane.
8. The novel self-adhesive metal-based integral catalyst coating according to claim 1, characterized in that: The cross-linking catalyst is a platinum catalyst; the platinum content of the platinum catalyst is 2500ppm to 6000ppm.
9. Application of the coating according to any one of claims 1 to 8 to a metal-based monolithic catalyst, characterized in that: The method for preparing the metal-based monolithic catalyst comprises the following steps: (A1) Weigh appropriate amounts of resin, carrier filler, and tackifier according to the ratio of raw materials; (B1) mixing the resin and the carrier filler in a power mixer, and grinding until the carrier filler is evenly dispersed; (C1) evacuating the mixture in step B in a power mixer and stirring evenly, cooling to room temperature, adding a tackifier and a coupling agent and mixing evenly, adding a catalyst and an inhibitor, and stirring evenly to obtain a self-adhesive catalyst coating precursor; (D1) spraying the mixture of step C on the treated substrate surface using a spray gun, and then drying at 80 to 120° C. for 5 to 180 min to obtain a metal honeycomb substrate-coating structure on the metal honeycomb substrate; (E1) The metal honeycomb substrate-coating structure is immersed in an excess active component salt solution for 0.5 to 10 hours, and dried in an oven at 50 to 150° C. for 2 to 15 hours to obtain a self-adhesive metal-based monolithic catalyst having catalytic activity; The preparation method may also include the following steps: (A2) Resin, carrier filler and tackifier weighed according to the ratio of raw materials; (B2) Immersing the carrier filler in the active component salt solution for 0.5 to 10 hours, and drying in an oven at 50 to 150° C. for 2 to 15 hours to obtain a carrier filler having catalytic activity. (C2) mixing the resin and the carrier filler having catalytic activity in a power mixer, and grinding until the carrier filler is evenly dispersed; (D2) evacuating the mixture in step C in a power mixer and stirring evenly, cooling to room temperature, adding a tackifier and a coupling agent and mixing evenly, adding a catalyst and an inhibitor, and stirring evenly to obtain a self-adhesive catalyst coating precursor; (E2) spraying the mixture of step D on the surface of the metal substrate using a spray gun, and then drying at 80 to 120° C. for 5 to 180 min to obtain a self-adhesive metal-based monolithic catalyst having catalytic activity; The active component precursor is one or more of nitrates, sulfates or chlorates of platinum, palladium, silver, manganese, nickel or other chemical elements.
10. The use of the coating in a metal-based monolithic catalyst according to claim 9, characterized in that: The weight loss rate of the metal-based integral catalyst is 0.22% to 0.81%, and the purification efficiency of toluene under water vapor conditions is above 90%.
Citation Information
Patent Citations
An electrically heated monolithic metal-based catalytic reactor and its preparation method
CN112999987B